2011
DOI: 10.5577/intdentres.2011.vol1.no3.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Menopause on Periodontal Tissue

Abstract: Periodontitis and gingivitis, a prevalent oral diseases, have been connected to several systemic health changes. The aim of this investigation was to review the effects of menopause on periodontal tissue. Epidemiologic studies have identified a number of risk factors and risk indicators for periodontal attachment loss, including demographic, socioeconomic, behavioural, genetic, and systemic factors. Menopause has also been associated with destructive periodontal disease in older women. The homeostasis of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…[1] After menopause, women become more susceptible to periodontal disease. [2] The homeostasis of the periodontium involves complex multifactorial relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] After menopause, women become more susceptible to periodontal disease. [2] The homeostasis of the periodontium involves complex multifactorial relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is associated with significant adverse changes in the orofacial complex. [1] As in progesterone level may change vascular permeability and then result in gingival swelling and inflammation and reduce resistance to dental plaque (i.e. bacteria).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of the treatment in periodontitis is to control bacteria as a local factor to minimise the systemic effects as a form of non-surgical treatment for periodontal disease. 6,7 Host modulation therapy (HMT) is part of a periodontal therapy that is used as an adjunct to conventional periodontal treatments such as scaling and root planning, and aims to reduce damage and regenerate the periodontal tissue by reducing the destructive aspects of the host response. 2,8 The HMT properties can be found naturally in lemuru fish oil.…”
Section: P G I N G I V a L I S B A C T E R I A S E C R E T E E N D O T O X I N Lipopolysaccharides (Lps)mentioning
confidence: 99%
“…Systemic bone loss may be considered as a risk indicator for periodontal destruction and elevated rates of loss of bone mineral density after menopause are associated with greater risk of tooth loss. [ 35 36 ] Osteoporosis is observed to cause bone destruction in the alveolar processes of the mandible and maxilla, which provide a bony framework for anchorage of the tooth. Even though the association between systemic osteoporosis and oral health remains controversial, it has been suggested that tooth loss in menopausal and postmenopausal women might signal the onset of systemic osteoporosis.…”
Section: Selection Of Datamentioning
confidence: 99%